Diferenciación geográfica del “otuno”, Diplomystes viedmensis Mac Donagh, 1931 (Pisces siluriformes) - Ringuelet, Raúl Adolfo (1965)
A re-examination of the typical material and some other specimens of the “otuno” from Mendoza (Argentina) and the Rio Negro is made. The typical subspecies in apparently restricted to the Rio Negro bassin. D. viedmensis cuyanus n. subsp., from Vilucó (Mendoza Province), in the Atuel bassin, is differentiated by several meristic measures and its ‘'Character-Index” of 11.4 and 11.5.